PERAN INDONESIA DALAM PERGOLAKAN KAPITALIS BARU: PLATFORM PENYEDIA JASA PENGINAPAN OYO HOTELS DAN REDDOORZ - Saputra, Hanafi (Journal of Humanity Studies, 2022)
This study reads the phenomenon of new platform capitalism from a sociological perspective. This study will critically discuss what is a platform based business model? How has the development of a platform based business model developed and has a positive impact on the Indonesian economy in the field of lodging services? and whether Indonesia is in the position of a player or even just as a worker in the digital economy era in the era of the industrial revolution 4.0, especially on the platforms of lodging service providers Oyo Hotels and RedDoorz. Furthermore, the authors can conclude that technological developments and economic globalization have given birth to a new form of capitalism, namely economic digitization in the form of platforms especially in the field of lodging service providers, namely Oyo Hotels and RedDoorz.